2010
DOI: 10.1099/ijs.0.013656-0
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter bereziniae sp. nov. and Acinetobacter guillouiae sp. nov., to accommodate Acinetobacter genomic species 10 and 11, respectively

Abstract: Acinetobacter genospecies (genomic species) 10 and 11 were described by Bouvet and Grimont in 1986 on the basis of DNA–DNA reassociation studies and comprehensive phenotypic analysis. In the present study, the names Acinetobacter bereziniae sp. nov. and Acinetobacter guillouiae sp. nov., respectively, are proposed for these genomic species based on the congruence of results of polyphasic analysis of 33 strains (16 and 17 strains of genomic species 10 and 11, respectively). All strains were investigated by sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
82
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 23 publications
3
82
0
2
Order By: Relevance
“…Although many species of Acinetobacter are reported as PGPR (Indiragandhi et al, 2008;Gulati et al, 2009;Kang et al, 2009;Shi et al, 2011), this SW5 strain showed a high plant growth promoting capability. SW5 strain has a 97.875% of sequence homology of 16S rRNA gene compared with the type strain A. guillouiae ATCC 11171 T reported recently by Nemec et al (2010), and some general characteristics of SW5 strain were coincided with those of other Acinetobacter spp. (Baumann et al, 1968).…”
Section: Resultsmentioning
confidence: 84%
“…Although many species of Acinetobacter are reported as PGPR (Indiragandhi et al, 2008;Gulati et al, 2009;Kang et al, 2009;Shi et al, 2011), this SW5 strain showed a high plant growth promoting capability. SW5 strain has a 97.875% of sequence homology of 16S rRNA gene compared with the type strain A. guillouiae ATCC 11171 T reported recently by Nemec et al (2010), and some general characteristics of SW5 strain were coincided with those of other Acinetobacter spp. (Baumann et al, 1968).…”
Section: Resultsmentioning
confidence: 84%
“…Reference strain Escherichia coli TOP10 was used as a host for clonings. A. bereziniae strain CIP70.12, isolated from a human wound in 1970, was used as the reference strain (15).…”
Section: Methodsmentioning
confidence: 99%
“…A. bereziniae is a Gram-negative, strictly aerobic, oxidase-negative, and nonmotile coccobacillus (15). A. bereziniae was found to be responsible for health care-associated infections, including severe sepsis in an immunocompromised patient (12).…”
mentioning
confidence: 99%
“…nov. (13), have previously been identified in clinical samples, they were subjected to studies of identification methods without mention of clinical relevance (10,15). In this study, we identified AGS 10 isolates from six blood samples.…”
mentioning
confidence: 96%